Memperkuat Fondasi Inklusi: Evaluasi Efektivitas PKM dalam Meningkatkan Pemahaman Konsep Pendidikan Inklusif di Kalangan Pendidik - Raden Roro Nanik Setyowati; Harmanto Harmanto; Budi Santosa; Rianda Usmi; Edy Suprianto; Beti Indah Sari; Rima Ristiarni (Jurnal Gema Ngabdi, 2026)
Inclusive education and child-friendly schools are essential approaches to ensuring equitable, safe, and supportive learning environments for all students, including children with diverse needs. This community service activity aimed to improve participants’ understanding of inclusive education and child-friendly school principles. The activity was conducted through a training program involving 27 participants. The evaluation was carried out using a pretest and posttest design consisting of 20 questions, with each correct answer assigned a score of 10 points. The data were analyzed descriptively by comparing the mean pretest and posttest scores and identifying changes in participants’ individual scores. The results showed that the mean pretest score was 90.56, while the mean posttest score increased to 97.04, indicating an average improvement of 6.48 points. In addition, 82% of participants demonstrated an increase in scores, and no participant experienced a decrease after the training. These findings indicate that the training activity contributed positively to strengthening participants’ understanding of inclusive education and child-friendly schools. This program is expected to support teachers, school leaders, and relevant stakeholders in implementing inclusive and child-friendly educational practices in school environments.